Risk factors for AA amyloidosis in Germany - Blank, Norbert; Hegenbart, Ute; Lohse, Peter; Beimler, Jörg; Röcken, Christoph; Ho, Anthony Dick; Lorenz, Hanns-Martin; Schönland, Stefan (Amyloid, 2015)
To identify risk factors for serum amyloid-A (AA) amyloidosis in patients living in Germany. Methods: Clinical and genetic data were obtained from 71 patients with AA amyloidosis. SAA1 genotypes were analyzed in 231 individuals. Control groups comprised 45 patients with long-standing inflammatory diseases without AA amyloidosis and 56 age-matched patients without any inflammatory disease.
Published online: 7 November 2014
Gesehen am 26.05.2020